2012
DOI: 10.1155/2012/904323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Modification on the Electrical, Structural, and Optical Properties ofTiO2Electrodes and Their Performance in Labscale Dye-Sensitized Solar Cells

Abstract: Carbon-modified titanium dioxide nanoparticles (C:TiO 2 NPs) have been synthesized by ultrasonic nebulizer spray pyrolysis (USP) and pneumatic spray pyrolysis (PSP) techniques. HRTEM on the NPs shows difference in lattice spacing in the NP structures prepared by the two methods-2.02Å for the USP NPs and an average of 3.74Å for the PSP NPs. The most probable particle sizes are 3.11 nm and 5.5 nm, respectively. Raman spectroscopy supported by FTIR confirms the TiO 2 polymorph to be anatase with the intense phono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
(37 reference statements)
2
25
0
Order By: Relevance
“…Modification of TiO 2 with metal and nonmetal elements has received much attention and Doped TiO 2 nanoparticles exhibit novel properties and according to impurity type, dopants improve the physical and optoelctronic paroperties of TiO 2 nanoparticles. For instance, K. Kaviyarasu et al 11 reported the fabrication, optical and microscopic studies of magnesium doped TiO 2 NCs .optical, structural, and electronic properties of carbon-modified titanium dioxide nanoparticles synthesized by ultrasonic nebulizer spray pyrolysis have been investigated by R. Taziwa et al 12 S. Ivanov et al 13 studied one-step synthesis of TiO 2 nanoparticles based on the interaction between thiourea and metatitanic acid and reported the photocatalytic activity of the doped SC-TiO 2 powders. TiO 2 nanoparticles in both powder and film form can be synthesized using various methods such as chemical vapor deposition 14 , chemical spray pyrolysis 15 , sol-gel technique 16 , hydrothermal treatment 17 , and arc discharge method 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Modification of TiO 2 with metal and nonmetal elements has received much attention and Doped TiO 2 nanoparticles exhibit novel properties and according to impurity type, dopants improve the physical and optoelctronic paroperties of TiO 2 nanoparticles. For instance, K. Kaviyarasu et al 11 reported the fabrication, optical and microscopic studies of magnesium doped TiO 2 NCs .optical, structural, and electronic properties of carbon-modified titanium dioxide nanoparticles synthesized by ultrasonic nebulizer spray pyrolysis have been investigated by R. Taziwa et al 12 S. Ivanov et al 13 studied one-step synthesis of TiO 2 nanoparticles based on the interaction between thiourea and metatitanic acid and reported the photocatalytic activity of the doped SC-TiO 2 powders. TiO 2 nanoparticles in both powder and film form can be synthesized using various methods such as chemical vapor deposition 14 , chemical spray pyrolysis 15 , sol-gel technique 16 , hydrothermal treatment 17 , and arc discharge method 18 .…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, the calculated HOMO-LUMO gap energies decrease slowly from 4.5 to 4.1 eV as the adopted cluster size goes from (TiO 2 ) 16 to (TiO 2 ) 60 . [25] Qu and Kroes reported the use of the lowest-lying isomer of the (TiO 2 ) 9 cluster to refer to the surface electronic structure of TiO 2 .…”
Section: Computational Modeling and Detailsmentioning
confidence: 99%
“…[7] Recently, various reformative TiO 2 modification methods (such as doping non-metal anions at O sites and metal cations at Ti sites) have been developed to construct DSSCs with high efficiency. It has been revealed that non-metal doping (e.g., B, [8] C, [9] N, [10] S, [11] and I [12] ) can induce additional electronic states above the valence band edge of the original TiO 2 but with a very small effect on the CB edge composed of Ti 3d orbitals. [13] In addition, nitrogen as a dopant in TiO 2 was found to be harmful to the stability of batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that these nano‐materials demonstrate desirable qualities such as excellently high responses, low cost, ease of miniaturisation and relatively fast recovery times at elevated temperatures. However, the high‐operating temperatures and poor selectivity of these metal oxides have led to new attempts to use carbon nano‐materials such as carbon nanotubes (CNTs) and graphene as alternatives in gas sensors, as well as hybrid materials of metal oxides and CNTs . However, to date these new carbon materials have not yet managed to find a significant industrial use.…”
Section: Introductionmentioning
confidence: 99%